Odpowiedzi

2010-02-21T12:13:16+01:00

x-pierwsza liczba =7
2x-9-druga liczba =2×7-9=14-9=5
12-suma tych liczb
x+2x-9-suma tych liczb
x+2x-9=12
3x=12+9
3x=21/:3
x=7
spr.:
7+5=12
chyba dobrze ;P
PoZDrawiam ^^
xD
1 5 1
2010-02-21T12:14:16+01:00
X - jedna liczba
y- druga liczba

(x=2y-9
(x+y=12

(2y-9+y=12
(3y=21

y=7
x=5

Proszę i liczę na naj :)
1 5 1
Najlepsza Odpowiedź!
2010-02-21T12:16:57+01:00
X- pierwsza liczba
y- druga z liczb

x+9=2y
x+y=12

x-2y=-9
-x-y=-12
______

-3y=-21
y=7
_____-
x+7=12
x=5
y=7

1 5 1